Preparation and Characterization of the Conductive Co(1-x)NixFe2O4/Polypyrrole Microsphere Composites - Zhang, Changsen; Yang, Lei; Wu, Qisheng; Luo, Juhua (Asian Journal of Chemistry, 2013)
Co(1-x)NixFe2O4 nanoparticles were synthesized by a sol-gel method and then the core-shell structure Co(1-x)NixFe2O4/polypyrrole nanocomposites, where the core was Co(1-x)NixFe2O4 and the shell was polypyrrole, were prepared by in situ polymerization. Phase composition, microstructure and magnetic properties of the samples were investigated by Fourier transform spectrometer, X-ray diffraction diffractometer, scanning electron microscope and superconductor quantum interference device. The results indicate that the average sizes of Co(1-x)NixFe2O4/polypyrrole nanocomposites are about 100 nm. The saturation magnetization of the pure Co(1-x)NixFe2O4 nanoparticles are 52.3 emu/g, but Co(1-x)NixFe2O4/polypyrrole composites are 37.36 emu/g. Both Co(1-x)NixFe2O4 and Co(1-x)NixFe2O4/PPy showed superparamagnetism.